Ecological dynamics of Mangifera L. (Anacardiaceae) in a Malaysia lowland rain forest. - Linatoc, A.C.; Ibrahim, Faridah Hanum; Latiff, A. (Forestry Department Peninsular Malaysia, 2011)
The study was carried out in the 50-ha forest dynamics plot of Pasoh Forest Reserve to obtain a quantitative evaluation of the abundance and diversity of the genus Mangifera in the Malaysian lowland rain forest. Twelve species including 1 variety of Mangifera accounting to a total of 1,202 stems were identified. M. quadrifida var. quadrifida obtained the highest count of 275 stems, followed by M. foetida with 208 stems, while M. swintonioides is the most rare represented by only two trees. The majority (70%) of the population is confined in the swampy area. M. quadrifida var. quadrifida obtained the highest biomass (0.51 tha-1) while it was M. griffithii that recorded the highest volume and basal area of 0.63 m3ha-1 and 0.045 m2ha-1, respectively. The relatively high density observed on small trees (seedlings and saplings) in the plot is likely related to the low density of larger trees.